Pengembangan Model Pembelajaran Membaca Permulaan melalui Metode Steinberg dengan Media Compic bagi Siswa Kelas II Sekolah Dasar - Lili Fajrudin, - (2020)
Beginning reading learning in elementary schools 21 and 03 in Serang City is good enough, but there are some things that are still lacking, namely the ability to read the beginning of students, students can only read words, easy, read, make, read, make, and read. pay attention to punctuation marks, in addition to the use of methods and models of learning to begin with reading in each school has not varied. For this reason the researcher tried to develop a model of beginning reading learning through the Steinberg method with Compic media to improve students' initial reading skills. Product design conducted by researchers using the Dick and Carey development method with 10 development, starting from making (1) Identifying the need to formulate objectives (2) Conducting subject matter analysis (3) Learning and context analysis (4) Explaining ability goals (5) Developing abilities learning instruments (7) Developing and selecting teaching materials (8) Developing and training formative evaluation (9) Learning revision programs and finally (10) Developing and planning summative learning. Then the finished product is tested for 40 students and 9 teachers. Based on the results of student and teacher responses can be assumed as a product development of reading learning models through the Steinberg method with Compic media created by researchers can be approved and appropriate. The product can be used in learning to begin reading in elementary school. Keywords: Steinberg Method, Media Compic, Reading Beginning